The principle of the immunity of states in the international community with an emphasis on the case of Germany and Italy - Seifpour, Sareh; Jalalian, Askar (Revista de la Universidad del Zulia, 2019)
The concept of judicial state immunity has changed due to international developments. This transformation has taken place in line with the international developments, including the limitation of the concept of  the sovereignty of  the states. In  the light of developments in international law, the sovereignty of the state is subject to several criteria, and today absolute sovereignty is unacceptable, and governments in many cases must be held accountable for their actions, so one of the most important of which is the observance of human rights standards. The basis of immunity is the sovereignty of the state. The purpose of this research is to study the principle of the immunity of countries in the international legal community. The main emphasis is on the subject of the Court’s ruling on the issue of Germany and Italy. The research has also been studied in descriptive and review methods and done in the library. In 2012, the International Court of Justice issued a verdict on the state immunity of the government in the German lawsuit against Italy. The Court reviewed the various aspects of the judicial immunity of the government and declared that the Italian Government issued a permit for a civil suit against Germany for violation of international humanitarian law by the Nazi Germany, the adoption of measures to enforce German property in Italy (Villa Vigoni), as well as by knowing the Greek judgments about the violation of humanitarian law in Greece by the Nazi Germany in the Italian courts, which it has breached its commitment to respect the immunities accorded by Germany to international law.